Birth Order and Intracranial Haemorrhage among Twin pairs in the Neonatal period. - Nzeh DÁ; Ajayi OA (Nigerian Journal of Paediatrics)
Summary: Transfontanelle ultrasound (US) was performed on 28 babies consisting of 14 twin pairs, to detect any intracranial hemorrhage (ICH). The mean birthweight (BW) of the babies was 1246 + 263gm (range 650 - 1700gm), while the mean gestational age was 31 +0.8 weeks (range 30-32 weeks). The mean age of the babies at the time of scan was 8 + 3 days (range 2-13 days). There was no significant difference (P>0.05) between the mean BW (1243+ 253gm (range 750 - 1700gm) of the first-born twins (group A) and that of the second-born twins (group B) (1250 + 282gm (range 650-1700gm). Intracranial hemorrhage was present in 7.1 percent of the group A twins and in 21.3 percent of the group B twins. These results show that BW alone was unlikely to make twin B babies more liable to ICH than twin A ones; the results also reinforce the proposition that the wellbeing of the second twin can be improved by skilful and properly co-ordinated management.